Direct Air Carbon Capture and Storage: A game changer in climate policy?; Direct Air Carbon Capture and Storage. Ein Gamechanger in der Klimapolitik? - Barbara Breitschopf; Elisabeth Dütschke; Vicki Duscha; Michael Haendel; Simon Hirzel; Anne Kantel; Sascha Lehmann; Frank Marscheider-Weidemann; Matia Riemer; Josephine Tröger; Martin Wietschel (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2023)
What is Direct Air Carbon Capture and Storage (DACCS) and could it be a game changer in climate policy? In this policy brief, we answer these and further questions.
Keywords: 330